Factors associated with access to food and essential medicines among Ugandans during the COVID-19 lockdown: a cross-sectional study - Elizabeth Katana; Bob Omoda Amodan; Lilian Bulage; Alex Riolexus Ario; Joseph Nelson Siewe Fodjo; Robert Colebunders; Rhoda Wanyenze (Journal of Interventional Epidemiology and Public Health)
Introduction: Many sub-Saharan African countries implemented lockdowns, curfew, and restricted movements among other strategies to control and prevent the spread of COVID-19. These measures caused problems of access to food and essential medicines. We evaluated the importance of this problem in Uganda.